Analysis of implementation of industry 4.0 principles in furniture production - Gayda, S.V.; Kushpit, A.S.; Huber, Yu.M. (Forestry, Forest, Paper and Woodworking Industry, 2023)
It is substantiated that the implementation of the principles of Industry 4.0 in the furniture industry will be able to significantly improve the competitiveness and efficiency of the enterprise, in particular, the replacement of workers with automated equipment in the manufacture of furniture will be able to increase the productivity and quality of production. It was found that the use of industrial robots and automated equipment can significantly reduce labor costs and increase production speed, and the introduction of sensors and their connection to the Internet can help monitor the condition of equipment, measure productivity and forecast maintenance needs. It was analyzed that the obtained data on production and interaction with clients will help in improving production processes and forecasting the demand for furniture products, and the use of virtual and augmented reality can significantly simplify the furniture design process and allow ideas to be implemented faster. It was found that the introduction of flexible production systems will allow to quickly switch to production between different types of furniture and respond to changes in demand. Also, the use of technological robots will be able to help reduce labor costs, especially in the face of growing demands for wages and labor shortages. It was found that the combination of physical and virtual systems will allow control and optimization of production processes in real time, and the use of machine learning algorithms for the analysis of large volumes of data can help identify and eliminate problems in furniture production, automate most production processes and reduce costs on the labor force. It is suggested to train personnel in advance for the introduction of new technologies - processing centers, technological robots, as this will help to ensure the successful and rapid implementation of the principles of Industry 4.0. Thus, robotics is a key element for the implementation of Industry 4.0 principles in furniture production, as it allows to increase the efficiency, quality and competitiveness of production.